Effect of Bovatec on grazing steer performance - Lyle W. Lomas (Kansas Agricultural Experiment Station Research Reports, 1982)
Steers fed 100 mg or 200 mg of Bovatec per head daily while grazing bromegrass gained 16.4% and 23.9% faster, respectively, during 112 days of grazing than did controls.
Keywords: Cattlemen& #x27; s Day; 1982; Report of progress (Kansas State University. Agricultural Experiment Station); 413; Beef; Steer Performance; Brome grass; Gain